Enhanced photocatalytic reduction of CO2 to CO over BiOBr assisted by phenolic resin-based activated carbon spheres. Issue 25 (8th May 2019) - Liu, Kangli; Zhang, Xiaochao; Zhang, Changming; Ren, Guangmin; Zheng, Zhanfeng; Lv, Zhiping; Fan, Caimei
Abstract : Photocatalytic reduction of CO2 using solar energy to decrease CO2 emission is a promising clean renewable fuel production technology. Abstract : Photocatalytic reduction of CO2 using solar energy to decrease CO2 emission is a promising clean renewable fuel production technology. Recently, Bi-based semiconductors with excellent photocatalytic activity and carbon-based carriers with large specific surface areas and strong CO2 adsorption capacity have attracted extensive attention. In this study, activated carbon spheres (ACSs) were obtained via carbonization and steam activation of phenolic resin-based carbon spheres at 850 °C synthesized by suspension polymerization. Then, the BiOBr/ACSs sample was successfully prepared via a simple impregnation method. The as-prepared samples were characterized by XRD, SEM, EDX, DRS, PL, EIS, XPS, BET, CO2 adsorption isotherm and CO2 -TPD. The BiOBr and BiOBr/ACSs samples exhibited high CO selectivity for photocatalytic CO2 reduction, and BiOBr/ACSs achieved a rather higher photocatalytic activity (23.74 μmol g −1 h −1 ) than BiOBr (2.39 μmol g −1 h −1 ) under simulated sunlight irradiation. Moreover, the analysis of the obtained results indicates that in this photocatalyst system, due to their higher micropore surface area and larger micropore volume, ACSs provide enough physical adsorption sites for CO2 adsorption, and the intrinsic structure of ACSs can offer effective electron transfer ability for a fast and efficient separation of photo-induced electron–hole pairs. Finally, a possible enhanced photocatalytic mechanism of BiOBr/ACSs was investigated and proposed. Our findings should provide new and important research ideas for the construction of highly efficient photocatalyst systems for the reduction of CO2 to solar fuels and chemicals.